Get Answers to all your Questions

header-bg qa

Provide Solutio for RD Sharma Class 12 Chapter 6 Adjoint and Inverse Matrix Exercise Fill in the blanks Question 20

Answers (1)

Answer   \rightarrow I

Given   \rightarrow A A^{T}=A^{T} A \text { and } B=A^{-1} A^{T}

Explanation    \rightarrow B=A^{-1} A^{T}

                   B^{-1}=\left(A^{-1} A^{T}\right)^{-1}

                    =\left(A^{T}\right)^{-1}\left(A^{-1}\right)^{-1} \qquad\left[(A B)^{-1}=B^{-1} A^{-1}\right]


               \begin{aligned} &B B^{-1}=A^{-1} A^{T}\left(A^{T}\right)^{-1}\left(A^{-1}\right)^{-1} \\ &=A^{-1} A^{T}\left(A^{T}\right)^{-1} A \\ &=A^{-1}\left(A A^{-1}\right)^{T} A \\ &=A^{-1} \cdot I \cdot A \end{aligned}

                =A^{-1} A=1             

                                      B B^{-1}=I 

Posted by


View full answer

Crack CUET with india's "Best Teachers"

  • HD Video Lectures
  • Unlimited Mock Tests
  • Faculty Support